Rola tlenku azotu w chorobach oka - Gerkowicz, Marek; Kosior-Jarecka, Ewa; Kozioł-Montewka, Maria (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Nitric oxide is a unique molecule with simple chemical structure and sophisticated and heterogeneous functions in human organism. In this article, we reviewed possible participations of nitric oxide in physiological and pathological states inside the eye (eg. glaucoma, cataract, uveitis and retinal disorders).